The quest for a framework for sustainable and institutionalised priority-setting for health research in a low-resource setting: the case of Zambia - Lydia Kapiriri; Pascalina Chanda-Kapata (BMC, 2018)
Abstract Background Priority-setting for health research in low-income countries remains a major challenge. While there have been efforts to systematise and improve the processes, most of the initiatives have ended up being a one-off exercise and are yet to be institutionalised. This could, in part, be attributed to the limited capacity for the priority-setting institutions to identify and fund their own research priorities, since most of the priority-setting initiatives are driven by experts. This paper reports findings from a pilot project whose aim was to develop a systematic process to identify components of a locally desirable and feasible health research priority-setting approach and to contribute to capacity strengthening for the Zambia National Health Research Authority. Methods Synthesis of the current literature on the approaches to health research prioritisations. The results of the synthesis were presented and discussed with a sample of Zambian researchers and decision-makers who are involved in health research priority-setting. The ultimate aim was for them to explore the different approaches available for guiding health research priority-setting and to identify an approach that would be relevant and feasible to implement and sustain within the Zambian context. Results Based on the evidence that was presented, the participants were unable to identify one approach that met the criteria. They identified attributes from the different approaches that they thought would be most appropriate and proposed a process that they deemed feasible within the Zambian context. Conclusion While it is easier to implement prioritisation based on one approach that the initiator might be interested in, researchers interested in capacity-building for health research priority-setting organisations should expose the low-income country participants to all approaches. Researchers ought to be aware that sometimes one shoe may not fit all, as in the case of Zambia, instead of choosing one approach, the stakeholders may select desirable attributes from the different approaches and piece together an approach that would be feasible and acceptable within their context. An approach that builds on the decision-makers' understanding of their contexts and their input to its development would foster local ownership and has a greater potential for sustainability.